Mechanism and Procedure of Repeated Borehole Drilling Using Wall Protection and a Soft Structure to Prevent Rockburst: A Case Study - Yongliang He; Mingshi Gao; Xu Dong; Xin Yu (Shock and Vibration)
With the increasing mining depth of coal mines, the occurrence of rockburst, especially in mine roadways, is becoming critical as a severe dynamic disaster. This paper explores the stability control of deep mine roadways and solves the contradiction between the support and pressure relief of roadways by studying the use of an internal steel pipe for wall protection and a soft structure for energy absorption during repeated borehole drilling. Numerical simulations are performed to examine the effects of active support technology on the support structure during repeated drilling. Internal steel pipes can effectively prevent the support structure from being damaged. When the soft structure cracks, the energy transmitted from the rockburst to the roadway is significantly reduced. According to the deformation and failure characteristics of the surrounding rock of the 21170 roadway, the combination of anchor active support, hydraulic lifting shed support, and soft structure energy absorption is proposed. An engineering case study shows that the support method can effectively maintain the stability of the surrounding rock and ensure the safe mining of the working face. The proposed control method can provide reference for the prevention and control of rockburst in mine roadways under similar geological conditions.